Quantifying the need and potential of assisted migration. (January 2017) - Hällfors, M.H.; Aikio, S.; Schulman, L.E.
Abstract: Assisted migration is recognized as a possible method for species conservation under climate change. Predicted decrease in range size and emergence of new suitable areas due to climate change are the main reasons for considering assisted migration. The magnitude of such changes can be used to guide decisions on the applicability of this conservation method. However, it has not been formalized how predictions acquired, e.g., with the help of species distribution models or expert assessments, should translate into recommendations or decisions. Climate change threat indices concentrating on predicted loss of habitat are not directly applicable in this context as they do not define whether a species has the potential to expand its range compared to the area that remains suitable. Here we present a conceptual framework for identifying and quantifying situations in which predictions indicate that a species could benefit from assisted migration. We translate predicted changes in suitable area into separate metrics for migration need and migration potential on the basis of the amount of lost, remnant, and new area. These metrics can be used as part of decision-making frameworks in determining the most suitable conservation method for a specific species. They also hold potential for coarser screening of multiple species to estimate the proportion of species that could benefit from assisted migration within a given time frame and climate change scenario. Furthermore, the approach can be used to highlight time frames during which assisted migration or, alternatively, other conservation actions are the most beneficial for a certain species. Highlights: Applicability of assisted migration can be quantified based on species' range changes. Loss of suitable area translates into migration need, gain into migration potential. The geometric mean of the need and potential provides the Assisted Migration Index. Threshold values link the AM Index to the Climate Change Vulnerability Index. Metrics presented can be utilized when considering conservation methods for species.